Recenzja z Fulvia Furinghetti, Alexander Karp (eds), Researching the History of Mathematics Education. An International Overview, Springer, 2018, ss. 314 +XV. - Błaszczyk, Piotr (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2019)
Recenzja